Economic and human development programs in the muslim world : a case study of the Islamic Development Bank (IDB) - Fakhri bin Sungit (International Institute of Islamic Thought and Civilization, Internationai Islamic University Malaysia, 2015)
This research examines the aims, objectives and achievements of the Islamic Development Bank (IDB) which was established for promoting the Islamic principles of brotherhood, solidarity and social justice among its Member Countries. The study involves inductive, deductive and descriptive methods in collecting and analyzing the data. The researcher employs library research to find selected documentations such as books, journals, theses and dissertations, articles, magazines, annual reports and the possible official documents and materials in the Bank. The stated objective of the IDB which is “to foster economic development and social progress of Member Countries and Muslim communities in non-Member Countries individually as well as jointly in accordance with the principles of Sharīcah”, is critically examined via the various activities and programs that have been carried out since its inception in 1975. The study analyzes the financing practices of the Bank that follow the guidelines of Sharīcah and maqāṣid based principles. The three dimensions of maqāṣid principles in the activities of Islamic banking and finance are evaluated namely, (i) Continuity of the Circulation of the Wealth, (ii) Continuity of the Investment of Wealth, and (iii) Achieving Comprehensive Communal Prosperity. The result shows that the Bank's objectives and development plans are in line with the principle of maqāṣid, but in reality the principles which are central to achieving social justice and public interests are still far from being realized. Thus, the study advices the Bank to reorganize the policies and orientation of the programs according to the outlook of the Islamic Human Development. Besides prioritizing the physical projects and development programs of economy, there should be space for the good governance and moral development through holistic educational programs and human capital venture.